Synthesis, characterization and electrochemical properties of novel pyridine phthalocyanine derivatives - (:unkn) unknown (WORLD SCI PUBL CO INC, 2018)
In this study, the novel Zn(II), metal-free and sandwich-type LuPc) 2 phthalocyanines containing tetra pyridine substituted at peripheral position were synthesized. All the new compounds have been characterized by FT-IR and UV-vis spectroscopy, H-1-NMR, MALDI-MS and elemental analysis. The electrochemical and spectroelectrochemical properties of all novel metallo- and metal free phthalocyanine compounds were also investigated by voltammetric and in situ spectroelectrochemical measurements on Pt in dimethylsulfoxide/tetrabutylammonium perchlorate.
Keywords: phthalocyanine; pyridine; bis-phthalocyanine; electrochemistry; spectroelectrochemistry; SENSING PROPERTIES; ZINC PHTHALOCYANINE; DECKER COMPLEXES; NANOSTRUCTURES; FLUORESCENCE; CATALYSIS; CO(II); MONO